In vitro cultivation and acclimatization of Miltonia flavescens (Lindl.) Lindl. with ora-pro-nobis extract (Pereskia aculeata Mill.) (Research, Society and Development, 2021)
The aim of this study was to evaluate the effect of aqueous ora-pro-nobis (Pereskia aculeata Mill.) extract on in vitro growth, survival rate, and acclimatization of Miltonia flavescens. Crude ora-pro-nobis extract was produced by infusing 10 g of dry leaves fractionated in 100 mL of distilled water. The treatments consisted of the crude extract (100%) and dilutions of 75%, 50%, and 25% added to Murashige and Skoog ½ culture medium (control treatment: absence of extract) where seedlings germinated in vitro were cultivated. After 270 days of cultivation, growth data were collected, and the plants acclimated. The survival rate was evaluated every 30 days, and the growth of the aerial part and root system were measured after 120 days of acclimatization. The data were submitted to analysis of variance and a test of the separation of means (Skott-Knott). For the number of leaves, the 100% treatment had the highest average value, differing statistically from the other treatments. For the length of the root system and fresh mass, the highest averages occurred in the control and 100% treatments. For the number of roots and shoots, there were no differences between treatments. After 120 days of acclimatization, plants from the 100% treatment had the lowest survival percentage, and plants from the 25% and 50% treatments had the greatest increase in the growth of the aerial part and root systems, demonstrating these treatments would be beneficial for the cultivation of this species.